OPTIMALISASI KONSUMSI AIR RUMAH TANGGA MENGGUNAKAN SISTEM PEMANTAUAN AIR PINTAR BERBASIS IOT - Fauzan Ishlakhuddin; Fachrul Pralienka Bani Muhamad; Eka Ismantohadi; Lucky Dawamuz Dzikri; Mohamad Muhgni Rahadiansyah; Ramadhani (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
This study develops an Internet of Things (IoT)-based Smart Water Monitoring System for periodic (near real-time) and comprehensive monitoring of household water consumption. The system consists of two main devices: a device for monitoring PDAM water flow rate and pressure using a YF-S201 flow sensor and a pressure sensor, and a device for monitoring water tank conditions using an SR04T ultrasonic sensor for water level measurement and a turbidity sensor for water clarity detection. Both devices are connected to ESP32/ESP8266 microcontrollers and transmit sensor data to a server every five minutes via a WiFi network. The implementation results indicate that the system is capable of performing stable sensor readings and data transmission during the household testing period, with consistent data delivery success and relatively low latency suitable for domestic monitoring purposes. Sensor evaluation was conducted using simple comparative methods, showing consistent measurement patterns after the initial calibration process. The collected data are visualized through web and mobile applications in the form of flow rate graphs, supply pressure graphs, water tank level charts, and turbidity indicators. This system has the potential to enhance the visibility of household water consumption and provides a technical foundation for early detection of water supply anomalies and the future development of data-driven water conservation systems.